Effect of Varying Levels of Fibrolytic Enzymes Supplementation on Digestibility of Nutrients and Plane of Nutrition in Gir Calves - Kadam, Sandip J; Garg, Deendayal; Savsani, Harish H; Patel, Sneh D; Patbandha, Tapas K; Karangiya, Vijay K; Sanchaniya, Jatin M (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The present study was conducted to investigate the effect of fibrolytic enzyme on digestibility of nutrients and plane of nutrition in Gir calves. Fifteen male Gir calves of around one year age were randomly divided into three groups with five calves in each and experiment was conducted for 90 days. Three TMR (total mixed ration, roughage: concentrate ratio 60:40) treatments used were: only TMR (T1), TMR supplemented with exogenous fibrolytic enzymes (EFEs, cellulase 10,00,000 IU/g and xylanase 1,50,000 IU/g in 1:1 ratio), at 0.025% of DM (T2) and at 0.050% of DM (T3). Digestibility (%) of dry matter (66.77 vs. 61.95), organic matter (70.18 vs. 66.58) and cellulose (58.54 vs. 53.40) were significantly (p<0.05) improved in T2 as compared to T1. Digestibility (%) of crude fibre (46.64 & 45.12 vs. 40.11), NDF (55.06 & 52.67 vs. 44.63), ADF (46.60 & 44.24 vs. 35.27) and hemicelluloses (79.69 & 77.22 vs. 71.90) were significantly (p<0.05) improved in both treatments (T2 & T3) as compared to T1. Results revealed that no significant effect was observed on DCP intake in both treatments as compared to control. TDN intake (kg/d) was significantly (p<0.01) increased in both T2 (3.51) and T3 (3.37) as compared to T1 (3.23). Based on overall results EFEs improved the intake and digestibility of nutrients of feed.